ZnO-Loaded SA-g-Poly (AC-co-EBS) Hydrogel Nanocomposite as an Efficient Adsorption of Tetracycline and Phenol: Kinetics and Thermodynamic Models - Aseel Mushtak Aljeboree; Mohammed Kassim Al-Hussainawy; Usama Salim Altimari; Shaymaa Abed Al-Hussein; Maha Daham Azeez; Ayad Fadhil Alkaim (Universitas Gadjah Mada, 2024)
A synthetic superabsorbent polymer hydrogel nanocomposite was prepared by the free radical graft co-polymerization method. This study included the preparation of two surfaces: first sodium alginate-g-(acrylic acid-co-sodium; 4-ethenylbenzenesulfonate), SA-g-poly (Ac-co-EBS) hydrogel, and second surface hydrogel after zinc oxide loading SA-g-poly (Ac-co-EBS). Hydrogel nanocomposite was prepared from different monomers for the removal of pollutants. The physical characterizations of nanocomposite have been studied using several techniques like UV-vis, FTIR, FE-SEM, TEM, EDX, and XRD. The data from the adsorption study show that E% increases with increasing contact time, with the best agitation time of 1 h, after which the adsorption becomes constant. The increase in adsorbent amount 0.01–0.1 g, the percentage removal of tetracycline (TC) and phenol (PH) increased from 60.639–97.085 and 487.71–94.05%, respectively, and Qe decreased 606.39–97.08 to 487.1831–94.456 mg/g on hydrogel. The ∆H value is endothermic. All processes of adsorption are considered spontaneous, from a negative value of ∆G to a positive value of ∆S. The release of the TC drug was studied in conditions similar to those in the human body in terms of acidity and temperature. The cumulative release of TC drug in 3 h was 50.65%, 42.33%, pH = 7.5 and pH 1.2, respectively.